Participation in the SUCCESS-A Trial Improves Intensity and Quality of Care for Patients with Primary Breast Cancer - Andergassen, U.; Kasprowicz, N. S.; Hepp, P.; Schindlbeck, C.; Harbeck, N.; Kiechle, M.; Sommer, H.; Beckmann, M. W.; Friese, K.; Janni, W.; Rack, B.; Scholz, C.; null (Geburtshilfe und Frauenheilkunde, 2013)
The SUCCESS-A trial is a prospective, multicenter, phase III clinical trial for high-risk primary breast cancer. It compares disease-free survival after randomization in patients treated with fluorouracil, epirubicin and cyclophosphamide followed by 3 cycles of docetaxel (FEC-D) with that of patients treated with 3 cycles of FEC followed by 3 cycles of gemcitabine and docetaxel (FEC-DG). After a second randomization patients were treated with zoledronate for 2 or 5 years. A total of 251 centers took part in the trial and 3754 patients were recruited over a period of 18 months which ended in March 2007. In a questionnaire-based survey we investigated the impact of enrollment in the trial on patient care, the choice of chemotherapy protocol and access to current oncologic information as well as overall satisfaction in the respective centers. Analysis of the 78 questionnaires returned showed that 40 % of the centers had never previously enrolled patients with these indications in clinical studies. Prior to participating in the study, 4 % of the centers prescribed CMF or other protocols in patients with high-primary breast cancer risk, 46 % administered anthracycline-based chemotherapy and 50 % gave taxane-based chemotherapy. Around half of the participating centers noted that intensity of care and overall quality of care became even better and that access to breast cancer-specific information improved through participation in the trial. After their experience with the SUCCESS-A trial, all of the centers stated that they were prepared to enroll patients in clinical phase III trials again in the future. These data indicate that both patients and physicians benefit from clinical trials, as enrollment improves treatment strategies and individual patient care, irrespective of study endpoints.
Keywords: gynecology; breast cancer; biomarker